FRI0064 Chemokine receptor 6 modulates arthritis in a t cell dependent manner. (15th June 2017) - Bonelli, M; Puchner, A; Goeschl, L; Hayer, S; Niederreiter, B; Smolen, JS; Scheinecker, C; Blueml, S
Abstract : Background: Rheumatoid arthritis (RA) is an inflammatory autoimmune disease, characterized by synovial infiltration of various cells. Chemokines are involved in the recruitment of different cell types into the synovial membrane. Accumulation of CCR6 expressing mononuclear cells can be found in joints of RA patients. CCR6 expression has also been reported on CD4 + T cells, in particular regulatory as well as Th17 cells. In addition, a subset of regulatory T cells, namely CD25 - Foxp3 + T cells, can upregulate CCR6 and RANKL and thereby can promote osteoclastogenesis. Objectives: In this study, we investigated the role of CCR6 in the pathogenesis of arthritis using different arthritis models. Methods: Clinical as well as histological signs of arthritis were investigated in the collagen-induced arthritis (CIA), K/BxN serum transfer arthritis and in the human tumor necrosis factor (hTNFtg) arthritis model, comparing wt and CCR6-/- mice. We analyzed the phenotype of lymph node cells by flow cytometry and cytokine concentrations in serum. Anti-collagen antibodies and cytokines were measured by enzyme-linked immunosorbent assay. Results: The K/BxN serum transfer arthritis and hTNFtg arthritis model are known to be T cell independent. Since CCR6 is an important component of the innate immune system we compared the development of arthritis in both models. We did not detect any significant differences in clinical signs of inflammation or histological severity of arthritis between wt and CCR6-/- mice. In addition, bone volume was similar between wt and CCR6-/- mice. To investigate the role of CCR6 as part of the adaptive immune system in the development of arthritis we induced CIA in wt and CCR6-/- mice, which is known to be T cell dependent. CCR6-/- mice were almost completely protected from CIA. Indeed, analyses of T cell subsets by flow cytometry revealed a significant reduction of CD25 - Foxp3 + T cells. Conclusions: CCR6 is necessary for the generation of pathogenic CD25 - Foxp3 + T cells in CIA, suggesting an important function of CCR6 on T cells in the development of autoimmune arthritis. Disclosure of Interest: None declared